Anti-Racist Pedagogy In and Against Lynching Culture - Ryan-Bryant, Jennifer Denise (Radical Teacher, 2018)
This article assesses the methodology and content of a graduate seminar on the literature of lynching, focusing on the inclusion of works by Ida B. Wells and a recent graphic novel, Mat Johnson and Warren Pleece’s Incognegro, as well as key assignments and discussion topics. After examining the events and history that inspired the course as well as its immediate cultural and social contexts, the article considers the questions that such literature raises for its readers and the next steps that it urges engaged students to take.